Staphylococcal nuclease folding intermediate characterized by hydrogen exchange and NMR spectroscopy. - Jacobs, M D (1994)
Pulsed hydrogen-deuterium exchange during refolding was used to probe the protection of backbone amide hydrogens from solvent exchange of the staphylococcal nuclease Pro117-->Gly variant. The extent of exchange for 39 residues was determined by two-dimensional proton NMR after refolding for 5 ms to 10 s. Three kinetic phases are inferred. Modest protection of amides in the early refolding intermediate composed of two beta-sheets formed by local sequence interactions was observed after a 5-ms refolding period. Protection factors were determined by varying the high pH labeling pulse after refolding for 100 ms. The intermediate state has modest, yet significant, protection for residues in the beta-sheets (protection factors of 10-60) and almost no protection in the alpha-helices (protection factors of < 10). The pattern of labeling is consistent with a role for beta-turns and beta-hairpins in the formation of the early intermediate.